On Kant’s Moral Philosophy and Its Contemporary Value - Yang, Jinguo (Journal of Social Science and Humanities, 2025)
Kant’s moral philosophy shows the characteristics of transcendentalism and purity, focusing on and emphasizing the motivation and result of behavior. This philosophical framework has had a profound impact on the development of the history of western philosophy. This paper first expounds the core idea of Kant’s moral philosophy as a starting point, and then deeply studies and probes into the three dimensions and concrete contents contained in his philosophical system. In addition, the article also analyzes the practical significance of Kant’s moral philosophy system in the development of contemporary society, and summarizes it.